2017
DOI: 10.1016/j.ajic.2017.06.034
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of half-mask elastomeric respirator and powered air-purifying respirator reprocessing for an influenza pandemic

Abstract: Background: Health care facilities are considering the use of reusable respiratory protective devices (RPDs) to mitigate a potential N95 filtering facepiece respirator shortage caused by an influenza pandemic. US regulators are also considering stockpiling reusable RPDs for pandemic preparedness, but limited data exist on the effectiveness of cleaning and disinfection of these devices. This study defines reprocessing protocols and evaluates their effectiveness against a pandemic influenza strain in a laborator… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
33
0
6

Year Published

2018
2018
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 28 publications
(39 citation statements)
references
References 18 publications
0
33
0
6
Order By: Relevance
“…During real-world contamination events, influenza virus could very likely be shielded by organic soiling agents like saliva or skin oil, which can inhibit the effectiveness of decontamination techniques. [27][28][29] The objective of the current study was to evaluate the UVGI decontamination efficiency of an intact FFR contaminated with both a pandemic influenza strain and a soiling agent to better simulate real-world contamination events. Fifteen N95 FFR models were contaminated with viable H1N1 influenza and either artificial saliva or artificial skin oil, then subsequently treated with UV light and evaluated for remaining viable virus.…”
mentioning
confidence: 99%
“…During real-world contamination events, influenza virus could very likely be shielded by organic soiling agents like saliva or skin oil, which can inhibit the effectiveness of decontamination techniques. [27][28][29] The objective of the current study was to evaluate the UVGI decontamination efficiency of an intact FFR contaminated with both a pandemic influenza strain and a soiling agent to better simulate real-world contamination events. Fifteen N95 FFR models were contaminated with viable H1N1 influenza and either artificial saliva or artificial skin oil, then subsequently treated with UV light and evaluated for remaining viable virus.…”
mentioning
confidence: 99%
“…The major limiting factor for the utilization of RERs by healthcare institutions is related to concerns about the cleaning and disinfection of such equipment. In a laboratory setting, the reprocessing protocols were defined by Lawrence et al [30]. They evaluated the effectiveness of this equipment for an influenza pandemic.…”
Section: Resultsmentioning
confidence: 99%
“…Forty-one surfaces were contaminated with the influenza virus, following which they were cleaned and disinfected. Lawrence et al [30] concluded that the methods they explained could be effective in cleaning and disinfecting influenza viruses. Moreover, these data might overcome some concerns regarding the effectiveness of the cleaning and disinfection of reusable respiratory devices such as half-or full-facepiece elastomeric respirators and PAPRs.…”
Section: Ijomeh 2021;34(2)mentioning
confidence: 99%
“…Derrick et al, 73 Rebmann et al, 74 Roberge et al, 75 Sinkule et al, 76 Shenal et al 69 (5) Reusable respirators [77][78][79][80][81][82][83] Fabrication or testing of reusable respirators that are meant to be decontaminated between uses.…”
Section: Discussionmentioning
confidence: 99%
“…Bessesen et al, 79 Hines et al, 81 Hines et al, 82 Hines et al, 83 Lawrence et al, 77 Pompeii et al, 80 Subhash et al 78 (6) Unconventional mask replacements or modifications 43-45 84 Assessment of cloth masks, new mask types, modifications of existing mask designs and use of non-medical equipment as masks.…”
Section: Discussionmentioning
confidence: 99%